Exposure to Influenza Virus Aerosols During Routine Patient Care - Bischoff, Werner E.; Swett, Katrina; Leng, Iris; Peters, Timothy R. (The Journal of infectious diseases, 2013)
Background. Defining dispersal of influenza virus via aerosol is essential for the development of prevention measures. Methods. During the 2010—2011 influenza season, subjects with influenza-like illness were enrolled in an emergency department and throughout a tertiary care hospital, nasopharyngeal swab specimens were obtained, and symptom severity, treatment, and medical history were recorded. Quantitative impaction air samples were taken not ≤0.305 m (1 foot), 0.914 m (3 feet), and 1.829 m (6 feet) from the patient's head during routine care. Influenza virus was detected by rapid test and polymerase chain reaction. Results. Sixty-one of 94 subjects (65%) tested positive for influenza virus. Twenty-six patients (43%) released influenza virus into room air, with 5 (19%) emitting up to 32 times more virus than others. Emitters surpassed the airborne 50% human infectious dose of influenza virus at all sample locations. Healthcare professionals (HCPs) were exposed to mainly small influenza virus particles (diameter, <4.7 μm), with concentrations decreasing with increasing distance from the patient's head (P < .05). Influenza virus release was associated with high viral loads in nasopharyngeal samples (shedding), coughing, and sneezing (P < .05). Patients who reported severe illness and major interference with daily life also emitted more influenza virus (P < .05). Conclusions. HCPs within 1.829 m of patients with influenza could be exposed to infectious doses of influenza virus, primarily in small-particle aerosols. This finding questions the current paradigm of localized droplet transmission during non—aerosol-generating procedures.